Opportunities for and challenges to a translingual approach to ELT in Brazil - William Mineo Tagata; Brenda Mourão Pricinoti; Guilherme Rodrigues Ferreira (Revista Brasileira de Linguística Aplicada, 2024)
Abstract: In this article we reflect upon the opportunities for and challenges to the implementation of a translingual approach in three different ELT contexts in Brazil, based on three autoethnographic accounts. The first account was written by an English teacher in early childhood bilingual education; the second, by an undergraduate English language and literature student and English teacher working in a private language school; the third, by a university professor in an English language and literature undergraduate course. In spite of their differences in terms of target audience, available resources for meaning production and ecological features in general, there seems to be a monolingual orientation pervading the three contexts. Despite the many challenges posed by this monolingual bias, which reflects the coloniality of power (MIGNOLO, 2000) and linguistic imperialism (PHILLIPSON, 1993, , 2009), the three authors believe in the importance of creating translingual spaces (GARCÍA; WEI, 2014) where students can negotiate their linguistic and cultural differences. This belief is grounded in the fact that in each context opportunities for translingual practices could be found and created.